ROMANTIC LOVE IN 'TWILIGHT': LOOKING AT THE ELEMENTS OF ROMANTICISM IN BELLA AND EDWARD'S RELATIONSHIP - Nisa, Zahrotun; Candraningrum, Dewi (Universitas Negeri Makassar, 2024)
The purpose of this study is to analyze the elements of romanticism contained in Bella and Edward's relationship in the film